Privacy-Preserving Techniques for Social Network Analysis - Mendonça, André L. C.; Brito, Felipe T.; Machado, Javam C. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2023)
With the increasing concerns over data privacy, preserving the privacy of individuals in social network analysis has become crucial. This tutorial provides a comprehensive overview of methods and techniques to protect individual privacy while conducting social network analysis. We perform a deep analysis of differential privacy, which is a rigorous mathematical framework to protect individual privacy while enabling accurate analysis of network structure and characteristics. Additionally, this tutorial explores a variety of examples and case studies to demonstrate the application of these techniques in practical scenarios.